Development of an instrumentation system embedded on FPGA for real time measurement of mechanical vibrations in rotating machinery - Da Costa, Cesar; Mathias, Mauro Hugo [UNESP]; Kashiwagi, Masamori [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The real-time monitoring of events in an industrial plant is vital, to monitor the actual conditions of operation of the machinery responsible for the manufacturing process. A predictive maintenance program includes condition monitoring of the rotating machinery, to anticipate possible conditions of failure. To increase the operational reliability it is thus necessary an efficient tool to analyze and monitor the equipments, in real-time, and enabling the detection of e.g. incipient faults in bearings. To fulfill these requirements some innovations have become frequent, namely the inclusion of vibration sensors or stator current sensors. These innovations enable the development of new design methodologies that take into account the ease of future modifications, upgrades, and replacement of the monitored machine, as well as expansion of the monitoring system. This paper presents the development, implementation and testing of an instrument for vibration monitoring, as a possible solution to embed in industrial environment. The digital control system is based on an FPGA, and its configuration with an open hardware design tool is described. Special focus is given to the area of fault detection in rolling bearings. © 2012 IEEE.
Keywords: ball bearings; fault diagnosis; reconfigurable architectures; vibration monitoring; Incipient faults; Industrial environments; Instrumentation systems; Manufacturing process; Monitoring system; New design; Open hardware; Operational reliability; Predictive maintenance; Real time measurements; Real time monitoring; Rolling bearings; Stator currents; Vibration monitoring; Vibration sensors; Ball bearings; Bearings (machine parts); Condition monitoring; Digital control systems; Failure analysis; Fault detection; Industrial plants; Instrument testing; Instruments; Reconfigurable architectures; Rotating machinery; Sensor networks; Vibration measurement; Vibrations (mechanical); Measurements